Imagens e representação do professor em Clarissa e Música ao longe, de Érico Veríssimo - Oliveira, Maria Marta Carrijo de (2013)
This work aims to a critical analysis of Erico Verissimo‟s first works Clarissa and Música ao longe. A well-known writer of the 30‟s, Erico Verissimo received many negative criticism because of the themes, characters and plot present in his works, as well as the ideological and psychological treatment given to the stories and his political and religious posture. Thus, we were concerned about how the relationship Character/writer is established, and what is the role of literature and the academic background in Verissimo‟s writings. We understand that every writer is formed by what he reads and how he fantasizes such works in his mind. These are marks that the reader, in one way or another, associates to the writer. This way, the creation of structures and meanings that overcome his writings have a relation to what the writer read in the past or still reads, no matter the kind of reading, for it has no end in itself, given the fact that literature is found in many places and many forms, not to mention the interpersonal relations and daily routines. From the analysis of the literary works in this dissertation, we will be able to see how the act of reading makes part of the characters‟ reality, realizing how the author works with subjectivity and representations on his literary works, as well as what is the importance given by him to an academic function from a literary perspective.